2009
DOI: 10.1097/mpa.0b013e31818d14a8
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of Thyrotropin-Releasing Hormone Receptors Activate Programmed Cell Death in Human Pancreatic Precursors

Abstract: Objectives Thyrotropin-releasing hormone (TRH) is expressed in rodent and human adult pancreas, and in mouse pancreas during embryonic development. However, expression of TRH receptors (TRHRs) in the pancreas is controversial. We sought to provide evidence that the TRH/TRHR system might play a role in fetal development. Methods We used quantitative RT-PCR to measure TRH and TRHR mRNA. To study the effects of TRHR expression in a pancreatic progenitor population, we expressed TRHRs in human islet-derived prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
(26 reference statements)
0
6
1
Order By: Relevance
“…Furthermore, it was suggested that the effect of TRH on glucose homeostasis is mediated, at least in part, by TRH-R1 expressed on insulin-secreting cells. It is noteworthy, therefore, that although TRH-R1 has been reported to be expressed in adult rodent islets at the mRNA and protein levels ( Kulkarni et al , 1995 ; Luo and Yano, 2004 ), we have found no TRH-R mRNA in islets of Langerhans from adult humans ( Mulla et al , 2008 ).…”
Section: Discussioncontrasting
confidence: 69%
“…Furthermore, it was suggested that the effect of TRH on glucose homeostasis is mediated, at least in part, by TRH-R1 expressed on insulin-secreting cells. It is noteworthy, therefore, that although TRH-R1 has been reported to be expressed in adult rodent islets at the mRNA and protein levels ( Kulkarni et al , 1995 ; Luo and Yano, 2004 ), we have found no TRH-R mRNA in islets of Langerhans from adult humans ( Mulla et al , 2008 ).…”
Section: Discussioncontrasting
confidence: 69%
“…On the other hand, TRHR is expressed not only in the pituitary but also in other tissues, including the testis 62 63 . Therefore, a possible contribution of altered paracrine action of TRH on testicular TRHR in the absence of IGSF1 may deserve consideration.…”
Section: Discussionmentioning
confidence: 99%
“…A relatively high (10 mM) TRH concentration mostly used in the present work is not physiological and it may potentially cause cell damage or death [37]. However, we have previously found that the addition of 10 mM TRH to the HEK293 cell line stably expressing TRH-R1 and G 11 m protein does not lead to apoptosis, although the cells stop growing [38].…”
Section: Discussionmentioning
confidence: 76%